Shariah Legal Practice in Nigeria 1956-1983 - Ajetunmobi, Musa Ali (Book collections on Project MUSE., 2018)
This book contains and in-depth study of the Shariah legal system generally, and its practice in Nigeria, in particular from 1956 to 1983. The book covers the meaning and scope of the Shariah: the general and legal precepts; it legal theory and legal practice; the development of Shariah legal practice and legal history in Nigeria.